Phylogeny and new taxonomy of the Booted Eagles (Accipitriformes: Aquilinae) - Lerner, Heather; Christidis, Les; Gamauf, Anita; Griffiths, Carole; Haring, Elisabeth; Huddleston, Christopher J.; Kabra, Sonia; Kocum, Annett; Krosby, Meade; Kvaløy, Kirsti; Mindell, David; Rasmussen, Pamela; et al. (Zootaxa, 2017)
We present a phylogeny of all booted eagles (38 extant and one extinct species) based on analysis of published sequences from seven loci. We find molecular support for five major clades within the booted eagles: Nisaetus (10 species), Spizaetus (4 species), Clanga (3 species), Hieraaetus (6 species) and Aquila (11 species), requiring generic changes for 14 taxa. Additionally, we recommend that the Long-crested Eagle (Lophaetus occipitalis) and the Black Eagle (Ictinaetus malaiensis) remain in their monotypic genera, due to their distinctive morphology. We apply the recently resurrected genus Clanga for the spotted eagles (previously Aquila spp.) to resolve the paraphyly of the genus Aquila such that the clade including the Booted Eagle (H. pennatus), Little Eagle (H. morphnoides), Pygmy Eagle (H. weiskei), Ayres’s Eagle (H. ayresii) and Wahlberg’s Eagle (H. wahlbergi) can remain in the genus Hieraaetus. The Rufous-bellied Eagle should be retained in the genus Lophotriorchis. For consistency in English names, we recommend that the term “hawk-eagles” be used only for the species in the genera Nisaetus and Spizaetus. We suggest following new or modified English names: Cassin’s Eagle (Aquila africana), Bonaparte’s Eagle (A. spilogaster), Ayres’s Eagle (Hieraaetus ayresii), and Black-and-chestnut Hawk-Eagle (Spizaetus isidori).